Pengaruh media sosial TikTok terhadap akhlak siswa di Madrasah Aliyah - Kurniasih, Melly; Subagiya, Bahrum; Amran (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
The massive use of TikTok social media among teenagers raises concerns about the moral development of students, especially in the context of relationships with teachers. This study aims to analyze the effect of using TikTok social media on the morals of grade XI students at MAN 1 Bogor Regency. The research approach used is quantitative with survey method. A total of 210 respondents were selected using purposive sampling technique. The research instrument is a five-point Likert scale questionnaire that measures the intensity of TikTok use and indicators of student morals towards teachers. The results of descriptive analysis show that the majority of students have a high intensity of TikTok use, but still show good moral tendencies. The simple linear regression test produced a significance value of 0.000 with a coefficient of determination (R²) of 14.9%, which means that there is a positive and significant influence between the use of TikTok on student morals. This finding confirms that the use of social media, especially TikTok, can contribute to students' character building, depending on the type of content consumed. Therefore, the active role of teachers and parents is needed in guiding students to use social media wisely to support the development of Islamic morals in the digital era. Abstrak Penggunaan media sosial TikTok yang masif di kalangan remaja memunculkan kekhawatiran terhadap perkembangan akhlak peserta didik, terutama dalam konteks hubungan dengan guru. Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan media sosial TikTok terhadap akhlak siswa kelas XI di MAN 1 Kabupaten Bogor. Pendekatan penelitian yang digunakan adalah kuantitatif dengan metode survei. Sebanyak 210 responden dipilih menggunakan teknik purposive sampling. Instrumen penelitian berupa angket skala Likert lima poin yang mengukur intensitas penggunaan TikTok dan indikator akhlak siswa terhadap guru. Hasil analisis deskriptif menunjukkan bahwa mayoritas siswa memiliki intensitas penggunaan TikTok yang tinggi, namun tetap menunjukkan kecenderungan akhlak yang baik. Uji regresi linear sederhana menghasilkan nilai signifikansi sebesar 0,000 dengan koefisien determinasi (R²) sebesar 14,9%, yang berarti terdapat pengaruh positif dan signifikan antara penggunaan TikTok terhadap akhlak siswa. Temuan ini menegaskan bahwa penggunaan media sosial, khususnya TikTok, dapat berkontribusi terhadap pembentukan karakter siswa, tergantung pada jenis konten yang dikonsumsi. Oleh karena itu, peran aktif guru dan orang tua sangat diperlukan dalam membimbing siswa menggunakan media sosial secara bijak demi mendukung pembinaan akhlak Islami di era digital.